Wear resistance improvement of 100CrMnSi6-4 bearing steel by laser boriding using CaF2 self-lubricating addition. (May 2016) - Piasecki, A.; Kulka, M.; Kotkowiak, M.
Abstract: Laser-alloyed layer with boron and CaF2 self-lubricating addition was produced on 100CrMnSi6-4 bearing steel. The produced layer was free of cracks or gas pores and uniform in respect of the thickness because of the high overlapping (86%). The microstructure consisted of re-melted zone and heat-affected zone. The re-melted zone included dendritic or globular iron borides with limited percentage of eutectic mixture in which CaF2 particles were located. Martensite and retained austenite occurred in heat-affected zone. Tribofilm, consisting of CaF2, was observed on the worn surface and was the reason for improved wear resistance compared to the laser-alloyed layer with boron only. In areas, in which tribofilm was thin or almost invisible, an intensive abrasive or oxidative wear proceeded. Graphical abstract: Highlights: Laser alloying introduced boron and CaF2 into the surface layer of bearing steel. Eutectic mixture of borides and martensite appeared in MZ, including CaF2 . CaF2 particles were vaporized, melted, re-solidified, or stayed in unchanged shape. Improved wear resistance resulted from tribofilm which was smeared on worn surface. Abrasive and oxidative wear appeared in areas, in which tribofilm was invisible.